Mesoeconomics of Migration and Trade - Bidabad, Bijan; Sherafati, Mahshid (International Journal of Business and Management Future, 2019)
In this paper, we analyze Mesoeconomics of migration and trade in interregional and international economy. Decision-makers are interested in analyzing how changing the prices or wages will lead to these movements and what policies can be devised to revert the markets into their initial equilibrium. We assume in our simple model, that the wages or prices change in one region, and we will measure the equilibrium of the markets of the two regions. After some time, by migration of workers and trading commodities, a new equilibrium will be achieved. If one of the governments of the two regions intends to revert the equilibrium to the state before changes were applied, how should that government act and how great will its financial burden be? In this paper, we try to formulate the answer to this question in the context of two simple, homogenous, and similar-shape economies. This paper is centered on the behavior of individuals of the two regions, which we try to generalize it so that we could evaluate the problem at meso level analytically. Therefore, we simplify the problem to the extent that its micro and macro dimensions coincide. We check different cases of Changing wage elasticity of price or production elasticity of employment and examine the financial burden of a policy of no labor and commodity movement. In this way, if the government of region 1 decides to counteract and revert the conditions into the previous state, it can pay specific subsidies to workers, legislate due taxes on selling commodities, and thereby establish the conditions of the equation as prior to changes.